Corruption perception index as an indicator of the level of corruption in an individual country and the world - I. A. Moiseeva (Russian Journal of Economics and Law, 2018)
Objective: to evaluate the methodology of corruption analysis based on the corruption perception index.Methods: the author used such sociological method as non-participant (simple) observation, methods of expert assessments and analysis of documents, grouping and summarizing; calculation of generalizing indicators; analysis; economic-mathematical and statistical techniques.Results: the corruption perception index, like any other method of studying corruption available in science, cannot be recognized as a universal indicator of its measurement. It does not meet the requirements of measurement reliability: the number of data sources and countries included in the index changed; new surveys emerged and some studies were discontinued; changes to the calculation methodology were made. Therefore, the only reliable technique is to compare the data on a particular state from the same specific source over a period of time. However, the author believes that the monitoring of changes of this indicator in a particular state may be important for assessing the achievement of the state’s tasks aimed at improving the investment climate.Scientific novelty: despite numerous studies of certain aspects of anti-corruption, the search for a universal method for evaluating the effectiveness of this struggle continues. Basing on the data studied by the author, a quantitative sociological-statistical assessment of the effectiveness of anti-corruption measures in the Republic of Belarus and neighboring countries is given. The article also substantiates the proposal to develop the anti-corruption index for the countries which are similar in the standards of doing business and a common understanding of national interests and methods of achieving them, namely the Customs Union, CIS, BRICS and SCO countries.Practical significance: the provisions and conclusions of the research can be used by the state authorities and public organizations for the formation and implementation of the state anti-corruption policy, as well as in scientific and educational activities for the study of methods of struggling against corruption.